Patient and practitioner satisfaction with tele-dermatology including Australia's indigenous population: A systematic review of the literature - Emily K. Kozera; Anes Yang, MD, BMed, MPH; Dedee F. Murrell, MA BMBCh FAAD MD FACD FRCP (Edin) (Wolters Kluwer, 2016)
Background: Australia's health disparity, combined with evolving technologies, has evoked increasing interest and funding in health services that could address inequities. One such emerging service is tele-medicine. Objective: The purpose of this report is to discuss and evaluate the current literature regarding patient and practitioner satisfaction with tele-medicine, and more specifically tele-dermatology. Methods: We searched for literature relevant to tele-dermatology use among Australia's indigenous population. We synthesized the literature in our report and identified elements of tele-dermatology not yet researched. Results: Most significantly, all available research is currently based on descriptive studies and there is no validated tool to assess the efficacy of tele-dermatology. Limitations: No published research currently exists on the use of tele-dermatology among Australia's indigenous population. Conclusion: A review of the literature shows that tele-dermatology is considered a valuable service, particularly to patients living in rural areas who might not otherwise have access to specialist care. Keywords: tele-dermatology, patient management, tele-medicine, dermatology, rural health, health technology